Case Report: Olaparib Shows Satisfactory Clinical Outcomes Against Small Cell Esophageal Carcinoma With ATM Mutation - Wang, Weiwei; Zhang, Xiaoyan; Fang, Yu; He, Jia; Huang, Jingjing; Li, Shanqing; Ma, Tonghui; Li, Li (Frontiers in Oncology, 2022)
Small cell esophageal carcinoma (SCEC) is a rare, undifferential type of cancer, with a high degree of malignancy and early systemic metastasis. Radio-chemotherapy and surgery have been used as the primary treatment strategies for SCEC, but they both result in poor prognosis. There is need to develop an optimal standard treatment for the disease to improve prognosis and limit the related mortality. In this study, we described identification of driver mutations in ATM, a gene involved in homologous recombination deficiency (HRD) pathway, using next-generation sequencing on primary lesion and peripheral blood of a SCEC patient, who experienced recurrence after resection and radio-chemotherapy. In addition, we subjected the patient to olaparib, a PARP inhibitor, for the treatment of tumor with HRD and obtained a partial response. This is the first evidence implicating olaparib in successful treatment of SCEC with ATM mutation. The findings suggest that targeting mutations in HRD genes using olaparib or actionable genetic mutations using corresponding drugs, may be an effective therapeutic option for SCEC, although this requires further investigation.